Controlling the Plastic Anisotropy of Magnesium Alloy by Tailoring the Grain Size and Yttrium Content - Mariyappan Arul Kumar; Marcin Wroński; Irene J. Beyerlein (Crystals, 2023)
Hexagonal close-packed (HCP) magnesium alloys are widely used in automotive and aerospace industries due to their low density and high specific-strength. Their applicability is mainly restricted due to poor formability and pronounced plastic anisotropy. The formability is usually improved by altering the chemistry (adding rare-earth elements like Y) or modulating the microstructure (e.g., grain refinement). However, grain refinement alone cannot yield the desired ductility, and the scarcity of rare-earth elements also limits the extent to which the alloying strategy can be used. To overcome these issues, in this work, it is proposed that the formability of Mg alloys can be improved by combining the grain refinement and alloying approaches. To quantitively explore this possibility, a crystal-plasticity-based constitutive model, which is sensitive to both alloying concentration and grain sizes, is developed. To demonstrate, the model is applied to study the combined effect of Y content and grain size on the mechanical responses of Mg alloy. The calculations are used to build maps of plastic anisotropy measures, such as tension–compression asymmetry ratio and Lankford coefficients, for a wide range of Y content and grain sizes. From these maps, the grain size that would yield the desired performance of Mg alloy for a fixed Y content can be identified. This work provides an accelerated pathway to optimize both the microstructure and chemistry simultaneously to achieve formability and to reduce the dependence on alloying.